Net debt supply shocks in the euro area and the implications for QE - Tobias Blattner; Michael A. S. Joyce (European Central Bank (ECB), 2016)
This paper examines how shocks to the net supply of government bonds affect the euro area term structure of interest rates and the wider macroeconomy. To measure net debt supply we construct a new free-float measure, which adjusts total government debt of the four largest euro area economies for foreign official holdings and the maturity of the outstanding stock of debt. Using a small macro-finance BVAR model, we estimate that the ECB's government bond purchases, as announced on 22 January 2015, reduced euro area 10-year bond yields, on average, by around 30bps in 2015 through the so-called duration channel. The impact on the output gap and inflation in 2016 is of the order of 0.2ppt and 0.3ppt respectively. Our estimates are likely to underestimate the overall impact of the ECB's purchases on interest rates and inflation, as they exclude effects on credit risk and monetary policy expectations that may have compressed interest rates even further.
Keywords: C5; E4; E5; G1; 330; ECB; government debt; macroeconomy; quantitative easing; term structure